PENGARUH UKURAN PERUSAHAAN, RETURN ON ASSET, DAN WINNER/LOSER STOCK TERHADAP PRAKTIK PERATAAN LABA - Iskandar, Andhika Fajar; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
This study aims to examine the factors that affect the income smoothing in Indonesia Stock Exchange (BEI) during the period 2010-2013. The sample used is manufacturing companies listed in Indonesia Stock Exchange listed until 2013 as many as 58 companies selected through a purposive sampling, so that the total number of observations with a 4-year study period was 232 observations. Variables tested in this study, namely the size of the company, return on assets, and the winner/loser stock. Based on data analysis techniques are logistic regression were performed in this study, the research results obtained show that the variable size of the company and the return on assets influence the practice of income smoothing, while the variable winner / loser stock no effect on income smoothing practices.
Keywords: income smoothing, company size, return on asset, winner/loser stock